Achene Morphology and Anatomy of Clematis L. (Ranunculaceae) in Korea and Its Taxonomic Implications - Balkrishna Ghimire; Beom Kyun Park; Dong Chan Son; Seung-Hwan Oh (Plants, 2020)
Clematis, a widely distributed genus in Ranunculaceae, is one of the most difficult groups of taxa in the family from a taxonomic point of view. A comprehensive study on achene morphology and the anatomy of 19 taxa of Clematis from Korea was carried out using scanning electron and light microscopy to evaluate the taxonomic significance of achene characters. Clematis achenes are elliptical, obovate or fusiform in shape, light yellow or brown to black in color and completely or sparsely covered with hairs. The permanent style is elongated and plumose in all the studied taxa except C. brachyura. We found that the size, indument, permanent style, surface sculpture, shape in cross-section, and nature and thickness of the exocarp, and endocarp were valuable achene features for species delimitation and may contribute to the unraveling of the taxonomic problems in the genus Clematis. One-way analysis of variance (ANOVA) indicated that the quantitative achene variables among the species were highly significant (p < 0.001). Principal component analyses based on seven quantitative characters and UPGMA (unweighted pair-group method with arithmetic mean) analysis based on seven quantitative and 18 qualitative characters also signify the utility of achene features for taxonomic discriminations of the Clematis taxa within the genus. Similar to other morphological characters in the genus Clematis, achene morphological and anatomical characters with the limited taxonomic value alone cannot be expected to resolve the infrageneric relationships but certain achene features combined with other morphological features could be useful as an alternative means of determining the infrageneric relationships within the genus.